Anticipating Intimacy or Sexual Victimization? Danger Cue Recognition and Delayed Behavioral Responses to a Sexually Risky Scenario. (April 2013) - Franklin, Cortney A.
This study used a sample of 257 female college students to investigate the heterogeneity of threat assessment, risk response, and delays in behavioral response, after the establishment of discomfort. Findings from three ordinary least squares (OLS) regression models indicated that (a) increased rape myth acceptance was correlated with threat assessment delays, (b) increased rape myth acceptance and prior verbally coercive sex were correlated with risk response delays, and (c) frequent pornography consumption and prior victimization were correlated with delayed behavioral response so that a woman remained in a risky sexual situation longer after establishing discomfort as compared to counterparts. Implications for research and policy are addressed.